Implementation of pH and TDS Sensor Automation Systems on Lettuce (Lactuca sativa L.) Growth in Hydroponic Cultivation - Putri, Gusti Dinia; Fevria, Resti; Vauzia, Vauzia; Violita, Violita (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
Lettuce (Lactuca sativa L.) is a vegetable commodity that is currently in high demand because it has many health benefits. Hydroponic cultivation is a method that can improve lettuce growth by utilizing IoT based pH and TDS sensors. This study aims to compare lettuce growth in hydroponic cultivation by applying Internet of Things (IoT)-based pH and TDS sensors and manual methods. The method used was an experimental method by comparing the average of two treatments, namely the use of IoT-based pH and TDS sensors and the manual method, with each treatment consisting of nine replicates. The results showed that the application of IoT sensors had a significant effect on increasing plant height, leaf area, wet weight, and dry weight. IoT technology can improve efficiency and productivity in hydroponic systems because the sensors can maintain a stable balance of nutrients and acidity in the solution, resulting in better plant growth. These findings indicate that the application of IoT has great potential in supporting sustainable agriculture, while also providing benefits in the form of increased production efficiency and resource savings.